1974
DOI: 10.1113/jphysiol.1974.sp010557
|View full text |Cite
|
Sign up to set email alerts
|

The carotid sinus baroreceptor reflex in the pregnant rabbit

Abstract: SUMMARY1. The reflex responses to baroreceptor stimulation have been compared in eight pregnant and eight non-pregnant anaesthetized female rabbits.2. The vascularly isolated, innervated carotid sinus was exposed for 30 sec to a series of non-pulsatile pressures ranging from 30 to 230 mmHg. The contralateral sinus nerve and both aortic nerves were cut. Systemic arterial pressure and heart rate were measured at each sinus pressure.3. The range of arterial pressure change which could be evoked from the isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
12
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
8
12
1
Order By: Relevance
“…Arterial blood gas tensions. As in our previous studies (Humphreys & Joels,-1974; Humphreyi & Joels, 1977), mean arterial PCO2 was lower in the pregnant animals. Mean arterial pressure.…”
Section: Methodssupporting
confidence: 68%
See 2 more Smart Citations
“…Arterial blood gas tensions. As in our previous studies (Humphreys & Joels,-1974; Humphreyi & Joels, 1977), mean arterial PCO2 was lower in the pregnant animals. Mean arterial pressure.…”
Section: Methodssupporting
confidence: 68%
“…Mean arterial pressure. Despite the more extensive operative interference, including laparotomy, required for these experiments, the levels of mean arterial pressure were similar to those recorded in previous studies on pregnant and non-pregnant rabbits (Humphreys & Joels, 1974, 1977.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…This change was first noted by Humphreys and Joels (97,98) in an extensive series of studies in anesthetized pregnant rabbits, in which reductions in carotid sinus pressure failed to elicit normal increases in arterial pressure and peripheral vascular resistance. Since then, arterial baroreflex impairment has been documented in several species studied in the conscious state, including dogs (23), rats (24,124), rabbits (21,97,162), goats (152), sheep (104,123), and humans (16,79,122,164,175,193). Reflex responses to atrial stretch are also blunted (51,94,95,103), which may contribute to retention of the expanded blood volume.…”
mentioning
confidence: 99%
“…First, both the arterial pressure and systemic vascular resistance are reduced (Humphreys & Joels, 1977 b;Nuwayhid, 1979); secondly, in the sympathectomized vascular bed of the hind limb smaller pressure changes occur in response to changes in blood flow, and this altered relationship persists when the sympathetic innervation is stimulated at fixed frequencies (Humphreys & Joels, 1982); thirdly, and probably as a consequence of the other changes, it has been shown that the increase of arterial pressure which can be evoked by lowering pressure within an isolated, innervated carotid sinus is reduced (Humphreys & Joels, 1974). Furthermore, Ladner, Brinkman, Weston & Assali (1970) have shown in the ewe that close to term the greatly enlarged uterine vascular bed is probably outside the control of the sympathetic vasomotor nerves, though so far this has not been demonstrated in the rabbit.…”
Section: Introductionmentioning
confidence: 99%